Home-Based Palliative Care Program Relieves Chronic Pain in Kerala, India: Success Realized Through Patient, Family Narratives - Aparna Sai Ajjarapu; Ann Broderick (Perm J, 2018)
An estimated 1.5 billion people across the globe live with chronic pain, and an estimated 61 million people worldwide experience unrelieved serious health-related suffering. One-sixth of the global population lives in India, where approximately 10 million people endure unrelieved serious health-related suffering. The state of Kerala is home to Pallium India, one of the most sophisticated palliative care programs in the country. This private organization in Trivandrum provides palliative and hospice care to underresourced populations and emphasizes holistic pain treatment. The current project features the pain stories of six patients who received treat- ment from Pallium India. Basic patient demographic information was collected, and a Pallium India staff member who was fluent in Malayalam and English asked questions about each patient’s pain experience. Pain narratives illustrate the substantial impact of Pallium India’s home visit program and the role of total pain assessment in delivering high-quality palliative care.